2015
DOI: 10.1021/acs.jpcc.5b01131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of SO2 Adsorption over the 1,3-Phenylenediamine/SiO2 System

Abstract: The reversible adsorption of SO 2 on 1,3-phenylenediamine was investigated using the step transient response technique coupled with operando infrared spectroscopy, mass spectrometry, UV−vis spectrometry, and density functional theory (DFT). At 50°C, the reaction of SO 2 at the amine site resulted in fixation of sulfur as hydrogen-bonded SO 3 2− (sulfite) and SO 4 2− (sulfate) species. Simulated infrared and UV−vis spectra at the DFT B3LYP/6-31G(d,p) level were compared to the experimental results to help chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
3
15
0
Order By: Relevance
“…The SO 2 reaction with amine groups occurs with the formation of electron donor-acceptor complexes between the acid and base [43]. The stability of such complexes is related to the amine basicity [44]. The stronger electron donating property of the methyl group is supposed to make MAPS a stronger base than the primary amine containing APS [45], but MAPS also has a higher steric hindrance than APS.…”
Section: Comparison Of Cyclic Stability Of Ca-s-aps With Ca-s-maps Inmentioning
confidence: 99%
“…The SO 2 reaction with amine groups occurs with the formation of electron donor-acceptor complexes between the acid and base [43]. The stability of such complexes is related to the amine basicity [44]. The stronger electron donating property of the methyl group is supposed to make MAPS a stronger base than the primary amine containing APS [45], but MAPS also has a higher steric hindrance than APS.…”
Section: Comparison Of Cyclic Stability Of Ca-s-aps With Ca-s-maps Inmentioning
confidence: 99%
“…8 In addition, the calculated interaction energies for SO 2 absorption range from À7.1 kcal mol À1 to À16.5 kcal mol À1 in the 1,3-phenylenediamine system. 58 It was also found that the adsorption energies range from À5.5 kcal mol À1 to À16.5 kcal mol À1 on polyphenylene based membranes. 5 These interaction energies as well as the current results imply a moderate interaction between SO 2 and the solvents.…”
Section: Energeticsmentioning
confidence: 95%
“…Furthermore, chemical interactions for the mechanism of SO 2 absorption/adsorption in other systems have been also reported. 19,58 However, NMR ( 1 H and 13 C) results show that SO 2 interacts physically with glycerol and the cation of ChCl. 25 This is not obviously contradictory with the current results, because the effects on the 1 H and 13 C NMR spectra may be negligible when the O-S and Cl-S bonds are formed.…”
Section: Structuresmentioning
confidence: 99%
See 2 more Smart Citations